FACTORS AFFECTING STUDENT LEARNING ACHIEVEMENT WITH E-LEARNING AS MODERATING VARIABLES - Iranda, Andy Dwiki; Rahmawati, Diana (Jurnal Pendidikan Akuntansi Indonesia, 2023)
This research aims to determine the effect of FoMO, Academic Stress, and Academic Burnout partially and simultaneously on Student Learning Achievement with the Use of Besmart e-learning as a moderating variable during the Covid-19 Pandemic. The population in this research were 258 students majoring in accounting education at YSU. Data collection techniques using a questionnaire. Test the validity of the instrument using the Product Moment correlation with 49 valid items and 5 falling items and the reliability test using Cronbach’s Alpha formula with the results of the variables FoMO, Academic Stress, and the Use of Besmart e-learning being very reliable and Academic Burnout reliable. The analysis prerequisite test includes normality test, linearity test, multicollinearity test, and heteroscedasticity test. Hypothesis testing consists of multiple regression and moderated regression analysis. The results of this research are FoMO has no effect on Student Learning Achievement during the Covid-19 Pandemic, Academic Stress has a negative effect on Student Learning Achievement during the Covid-19 Pandemic, and Academic Burnout has a negative effect on Student Learning Achievement during the Covid-19 Pandemic. Keywords: Student Learning Achievement, FoMO, Academic Stress, Academic Burnout, e-learning Besmart